2017
DOI: 10.1051/0004-6361/201731370
|View full text |Cite
|
Sign up to set email alerts
|

Detailed chemical composition of classical Cepheids in the LMC cluster NGC 1866 and in the field of the SMC

Abstract: Context. Cepheids are excellent tracers of young stellar populations. They play a crucial role in astrophysics as standard candles. The chemistry of classical Cepheids in the Milky Way is now quite well-known. Despite a much larger sample, the chemical composition of Magellanic Cepheids has been only scarcely investigated. Aims. For the first time, we study the chemical composition of several Cepheids located in the same populous cluster: NGC 1866, in the Large Magellanic Cloud (LMC). To also investigate the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 131 publications
4
23
0
1
Order By: Relevance
“…These values are in good agreement with the values from Romaniello et al (2008) with a slight offset of +0.03 dex leading to mean abundances of the combined samples of −0.73 ± 0.02 and −0.33 ± 0.03 dex respectively. Molinaro et al (2012) also measured metallicities for three Cepheids in NGC1866 and found a mean value of −0.40 ± 0.04 in good agreement with the value of −0.36 ± 0.03 from Lemasle et al (2017). Lemasle et al (2013) has similarly determined abundances for Milky Way Cepheids and for 12 stars in common with our sample the average metallicity is −0.07 ± 0.04 dex.…”
Section: Metallicitiessupporting
confidence: 76%
“…These values are in good agreement with the values from Romaniello et al (2008) with a slight offset of +0.03 dex leading to mean abundances of the combined samples of −0.73 ± 0.02 and −0.33 ± 0.03 dex respectively. Molinaro et al (2012) also measured metallicities for three Cepheids in NGC1866 and found a mean value of −0.40 ± 0.04 in good agreement with the value of −0.36 ± 0.03 from Lemasle et al (2017). Lemasle et al (2013) has similarly determined abundances for Milky Way Cepheids and for 12 stars in common with our sample the average metallicity is −0.07 ± 0.04 dex.…”
Section: Metallicitiessupporting
confidence: 76%
“…Grids have been calculated for a range of metallicities with that for an LMC metallicity being used here. As discussed by Dufton et al (2005), the atmospheric structure depends principally on the iron abundance with a value of 7.2 dex having been adopted for the LMC; this is consistent with estimates of the current iron abundance for this galaxy (see, for example, Carrera et al 2008;Palma et al 2015;Lemasle et al 2017). However we note that, although tests using the Galactic (7.5 dex) or SMC (6.9 dex) grids led to small changes in the atmospheric parameters (primarily to compensate for the different amounts of line blanketing), changes in element abundances estimates were typically less than 0.05 dex.…”
Section: Methodssupporting
confidence: 70%
“…Different authors found slightly different values for the metal content in the cluster. Lemasle et al (2017) in their spectroscopic analysis of a sample of Cepheids in the cluster, found a very homogeneous chemical composition of [Fe/H] = −0.36 ± 0.03 dex, in agreement with previous measurement of the red giant branch stars by Mucciarelli et al (2011). The MS presents a third main feature: its extension as a broad strip towards redder colours and brighter magnitudes (the dark points in the inset of Fig.…”
Section: Ngc 1866 Photometrysupporting
confidence: 88%
“…The case of NGC 1866 has been studied recently by many authors (e.g. Milone et al 2017;Goudfrooij et al 2018), and the common findings are that both rotation and different ages are required to explain the double MS and the eMSTO at Lemasle et al (2017).…”
Section: Ngc 1866 Photometrymentioning
confidence: 99%